Estimating frontline health workforce for primary healthcare service delivery in Bauchi State, Nigeria. (13th April 2021) - Okoroafor, S C; Ongom, M; Mohammed, B; Salihu, D; Ahmat, A; Osubor, M; Nyoni, J; Dayyabu, H; Alemu, W
ABSTRACT: Background: In Nigeria, adoption of the primary healthcare approach led to the establishment of numerous primary healthcare facilities, and training of new cadres of community health officers (CHOs), community health extension workers (CHEWs) and junior community health extension workers (JCHEWs). These new groups complemented the work of nurses and midwives. Methods: We conducted a workload indicators of staffing needs study in the 20 local governments of Bauchi State, from March 2016 to September 2018, in all 317 ward-level primary healthcare facilities. Results: Findings show a total of 128 existing nurses/midwives, a calculated requirement of 402 and a shortage of 274 nurses/midwives. Existing CHOs/CHEWs were 735, a calculated requirement was 948 and a shortage of 213 CHOs/CHEWs. The JCHEWs were 477, a calculated requirement of 481, with a shortage of four JCHEWs. Conclusion: Results from this study highlight the unequal distribution of health workers; the abundance of some frontline workers in some communities and dire need of others. We emphasize the need to strengthen health workforce planning to deliver essential primary healthcare services, particularly in rural and remote communities with high levels of vulnerability to diseases.